Liar, Liar - Patterson, James, 1947-; Fox, Candice (New York : Grand Central Publishing, 2020)
While on the run from the law, detective Harriet Blue, who is searching for her brothers killer, becomes his next target.
Keywords: Blue, Harriet -- (Fictitious character) -- Fiction; Women detectives -- Australia; Fiction; Fugitives from justice -- Fiction; Siblings -- Fiction; Serial murderers -- Fiction; Murder -- Investigation; Fiction; Sydney (N.S.W.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction